Assessing Changes in Fear of Movement in Patients attending Cardiac Rehabilitation: Responsiveness of the TSK-NL Heart Questionnaire - Nienke ter Hoeve; Paul Keessen; Iris den Uijl; Bart Visser; Roderik A. Kraaijenhagen; Madoka Sunamura; Wilma J. M. Scholte op Reimer; Corine H. M. Latour; Harald T. Jørstad; Hendrika J. G. van den Berg-Emons (Medical Journals Sweden, 2022)
Objectives: The primary objective was to determine the responsiveness of the Dutch version of the 13-item Tampa Scale for Kinesiophobia for cardiac patients (TSK-NL Heart). The secondary objective was to assess changes in kinesiophobia during cardiac rehabilitation. Methods: Kinesiophobia was measured pre- and post-cardiac rehabilitation using the TSK-NL Heart questionnaire in 109 cardiac patients (61 years; 76% men). The effect size of kinesiophobia score changes was calculated for the full population. A measure that is responsive to change should produce higher effects sizes in patients in whom kinesiophobia improves. Therefore, effect sizes were also calculated for patients who did or did not improve on selected external measures. For this step, the Cardiac Anxiety Questionnaire (CAQ) and the Hospital Anxiety and Depression Scale (HADS) were completed as external measures in a subsample of 58 patients. Results: The effect size of the TSK-NL Heart for the full study population was small (0.29). In line with the study hypothesis the effect size was higher (moderate) for patients with improved CAQ (0.52) and HADS scores (0.54). Prevalence of high kinesiophobia levels decreased from 40% pre-cardiac rehabilitation to 26% post-cardiac rehabilitation (p = 0.004). Conclusion: The TSK-NL Heart has moderate responsiveness and can be used to measure changes in kinesiophobia. Improvements in kinesiophobia were observed during cardiac rehabilitation. Nevertheless, high levels of kinesiophobia were still highly prevalent post-cardiac rehabilitation. LAY ABSTRACT Fear of movement (kinesiophobia) is common in patients referred for cardiac rehabilitation. Before interventions can be designed to target kinesiophobia, the impact of current cardiac rehabilitation programmes on kinesiophobia should be studied. Kinesiophobia is measured with the Tampa Scale for kinesiophobia (TSK-Heart). In order to measure the effect of cardiac rehabilitation on kinesiophobia, the TSK-Heart should be able to detect changes in the level of kinesiophobia (responsiveness). This study determined the responsiveness of the TSK-Heart and assessed changes in the level of kinesiophobia during cardiac rehabilitation, and shows that the TSK-Heart has moderate responsiveness. In addition, it was found that the prevalence of high levels of kinesiophobia, decreased from 40% before cardiac rehabilitation to 26% after cardiac rehabilitation.